Calibrated ages of Lebel (BC1A) peat core from Canada - Nicole K Sanderson; Arabelle Sauvé (PANGAEA, 2021)
Calibrated ages of a high-resolution peat core from the Past Global Changes - Carbon in Peat on EArth through Time (PAGES_C-PEAT) Project.